PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS WEB MODEL KOOPERATIF TIPE STAD DENGAN APLIKASI MOODLE SUB POKOK BAHASAN SEGITIGA UNTUK SISWA SMP KELAS VII - Sholihah, Siti Mar’atus; Slamin, S; Dafik, D (Department of Mathematics Education , University of Jember, 2014)
Abstract.Web based learning is attractive and innovative learning that can be used in class. The goal of the research is to know about process and result of developing of mathematics learning instrument based on web cooperative model type STAD with moodle application for triangle topic grade VII junior high shool. The research used developmental model Plomp. The subject of the research is student of VIIA in MTs Al Qodiri I Jember for even semester 2012/2013 academic year. The datas is validation sheets, activities of student and teacher’s observation sheets, questionner,and evaluation test. The products of the research are lesson plan, student worksheet, student book, evaluation test, and learning media.The result of this research is the learning instrument that developed is valid, pragmatic, and effective. Key Words:STAD, e-learning, LMS Moodle, triangle